Penerapan Asas Itikad Baik dalam Menjamin Profesionalitas Konsultan Desain pada Kontrak Konstruksi Design & Build di Indonesia - Pakpahan, Petra Firman; Sami’an, Sami’an; Hardjomuljadi, Sarwono; Aditya, Agung (Jurnal Impresi Indonesia, 2026)
The Design & Build (DB) procurement model reshapes the legal structure of construction contracts by consolidating the responsibility for both design and construction under a single entity, the DB contractor. Within this structure, design consultants operate under the contractor’s authority and have no direct contractual relationship with the owner, creating potential conflicts of interest that may compromise professional independence. This normative legal research examines how the principle of good faith and the statutory principle of professionalism can be employed to interpret and regulate the obligations of DB contractors and their design consultants, particularly in ensuring the integrity and reliability of design outcomes. Using a statute-based and conceptual approach, this study analyses the Indonesian Civil Code, Law No. 2 of 2017 on Construction Services, and doctrinal writings on contract law and construction law, alongside academic literature on DB performance. The findings reveal that good faith functions as an interpretive, supplementary, and corrective principle in contractual relationships, and can therefore serve as a normative foundation to prevent undue interference by contractors in design decisions. Furthermore, the principle of professionalism requires design consultants to uphold technical standards and ethical responsibilities, even when positioned hierarchically under the contractor. The study concludes that the integration of good faith and professionalism offers an effective normative mechanism to strengthen accountability in DB projects, protect the owner’s interests, and fill the contractual gap arising from the absence of privity between the owner and the design consultant.